Arabska Wiosna, „algierska zima”. Analiza kampanii wyborczej w czasie wyborów prezydenckich w Algierii (17.04.2014) - Kobis, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
Article aims to provide the reader with the specifics of non-European political systems on the example of the presidential elections in Algeria. Although the election campaign alluded to Western standards, the election results confirmed the pre-election speculation. The unquestionable victory of the seventy-seven-year-old Abdelaziz Buteflika shows that power in Algeria is still in the hands of the old generation of politicians, harking back to the times of the War of Independence from the years 1954 to 1962. The article presents an analysis of the statements of the Constitution relating to the position of the President of the State, and a brief description of the current presidential elections in Algeria. It also presents the candidates and their manifestos in the campaign of 2014. The article ends with conclusions which show the internal and external factors affecting the stability of the Algerian political regime and examines the possible effects of the Buteflika’s victory for security in the Mediterranean region and the European Union.
The Arab Spring, “the algerian winter”. An analysis of the election campaign during the presidential election in Algeria (17.04.2014)
Keywords: Algeria; elections; democracy; the European Union; “Arab Spring”